TINGKAT KETIMPANGAN PENDAPATAN PETANI KELAPA SAWIT DI DESA SEI JAWI-JAWI KECAMATAN PANAI HULU KABUPATEN LABUHAN BATU - Jimmi Candro Pakpahan; Leonardus Ricky Rengkung; Theodora Maulina Katiandagho (AGRI-SOSIOEKONOMI, 2021)
This research aims to analyze the level of  income disparity of oil palm farmers in Sei Jawi-Jawi Village, Panai Hulu District, Labuhan Batu Regency. This research was conducted from April to May 2021. The data used in this study are primary data and secondary data. Primary data is obtained by direct interview to 38 respondents using  questionnaires. secondary data obtained from government agencies, or institutions related to this research. The research is carried out by using surveys method and data analysis used to calculate the level of  income disparity of farmers was the Gini Ratio and World Bank. The research result showed  that the level of income disparity of oil palm farmers, based on Gini Ratio, was 0.32 and 0,28, which was in low category.